Troy Paper - Some Notes and Tests of an Open-hearth Steel Charge made for Boiler-plate. - Alfred E. Hunt (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1884)
The charge to be described was made in a seven-ton furnace, with a hearth twelve feet long and eight feet wide, with three gas and three air ports on each side. The stock of the entire heat was charged cold in one hour and five minutes, a part of the pig being first placed upon the bottom to protect it, then upon it the plate-scrap and blooms, and finally the remainder of the pig—some two thousand pounds. In fire hours and twenty-five minutes after beginning the charge the metal was melted down level, and two hundred pounds of hot twelve-per cent. spiegel was charged, care being taken to have it entirely immersed in the bath. In two hours more the bath was thoroughly melted and hot, and began to boil, i. e., the carbon began to be oxidized and evolved through the bath of covering slag as carbonic acid and carbonic oxide gases. Seventy-five pounds of lumps of Republic specular iron ore were added at this time, increasing the action, so that in ten minutes after the metal was in active ebullition. A test of the metal showed it to have about 0.90 per cent. carbon. One hour after the first ore was added a test was again taken, after thorough rabbling of the metal, and it was found to be 0.37 per cent. carbon. One hundred pounds more of lump Republic ore and about seventy-five pounds of limestone were then added, and fifty minutes later, after the bath was thoroughly rabbled, a -test showed the metal to have 0.23 per cent. carbon. Twenty-five pounds more of Republic iron ore were added and the metal allowed to boil for twenty minutes, when a test, after rabbling, showed the carbon to be 0.18 per cent. and the manganese to be 0.01 per cent.; the slag fracture was vitreous and of a very dark-green color. About forty pounds of limestone were added, and, the metal being hot and in a state of quiet ebullition, a hickory pole of twelve feet length and about four inches diameter, was run through the aperture in the centre door and held in a steady inclined position in the bath, with the end touching the bottom, the pole being shoved in further as it was burned away. The bath was carefully watched to see that the action that ensued was not too violent, the pole being several times